Biochar production from aquatic residues and its application in aquaculture - Mary Febna A. A. (KUFOS, 2018)
Abstract- Conversion of water hyacinth into useful products is a sustainable way to address the menaces created by water hyacinth along with exploration of beneficial applications. This work focuses on conversion of water hyacinth into climate a resilient product ‘biochar’ and its applications on pokkali paddy, tilapia fish and water quality in culture systems. Biochar was produced by pyrolysis technique in a muffle furnace with water hyacinth, Eichhorniacrassipes as substrate. The elemental composition of the generated biochar was analyzed by CHNS analyzer. The structural characterization of biochar was done using FTIR, XRD and SEM. Biochar profiling throw light on the morphological changes and chemical transformations occurred due to pyrolysis. Optimum pyrolysis conditions were finalized and accordingly used for production of sufficient quantities of biochar and for further experimentation. Biochar in varying ratios of 1, 2, 3, 4 and 5% were mixed with soil samples and the effect of biochar amended soil on pokkali growth was studied. Growth profile was monitored with parameters such as root length, shoot length and plant height. Highest growth performances were observed in 4% biochar-soil mixture system in comparison to the control. Biochar was incorporated into the feed of tilapia, Oreochromismossambicus in the ratio of 0.5 and 1 % and was fed to the fishes grown in tanks. The length and weight of tilapia fishes fed with biochar mixed feed were monitored for six weeks to assess the effect of biochar feed on fish growth. Weight and length of the fish were found to be enhanced significantly in biochar mixed feed and the highest was recorded for 1% of biochar mixed feed system. The water quality profiles of the biochar mixed feed system and for biochar-soil mixed system were also assessed. Slight changes were observed for pH, dissolved oxygen and total alkalinity. The results of biochar experimentation are promising and the work could be considered as a milestone towards further optimization and field level experimentation. The work demonstrates new horizons towards aquaculture application using biochar generated from water hyacinth.